Effect of supercritical CO2 on the copolymerization behavior of cyclohexene oxide/CO2 and copolymer properties with DMC/Salen‐Co(III) catalyst system. Issue 17 (6th June 2016) - Meng, Qing‐Yang; Pepper, Katie; Cheng, Rui‐Hua; Howdle, Steven M.; Liu, Bo‐Ping
ABSTRACT: The copolymerization of cyclohexene oxide (CHO) and carbon dioxide (CO2 ) was carried out under supercritical CO2 (scCO2 ) conditions to afford poly (cyclohexene carbonate) (PCHC) in high yield. The scCO2 provided not only the C1 feedstock but also proved to be a very efficient solvent and processing aid for this copolymerization system. Double metal cyanide (DMC) and salen‐Co(III) catalysts were employed, demonstrating excellent CO2 /CHO copolymerization with high yield and high selectivity. Surprisingly, our use of scCO2 was found to significantly enhance the copolymerization efficiency and the quality of the final polymer product. Thermally stable and high molecular weight (MW) copolymers were successfully obtained. Optimization led to excellent catalyst yield (656 wt/wt, polymer/catalyst) and selectivity (over 96% toward polycarbonate) that were significantly beyond what could be achieved in conventional solvents. Moreover, detailed thermal analyses demonstrated that the PCHC copolymer produced in scCO2 exhibited higher glass transition temperatures ( Tg ∼ 114 °C) compared to polymer formed in dense phase CO2 ( Tg ∼ 77 °C), and hence good thermal stability. Additionally, residual catalyst could be removed from the final polymer using scCO2, pointing toward a green method that avoids the use of conventional volatile organic‐based solvents for both synthesis and work‐up. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 2785–2793 Abstract : ScCO2 dramatically facilitates CO2 /CHO copolymerization, especially in reaction efficiency, selectivity to carbonate linkages and Tg of obtained PCHC. The phase changes of PCHC under different scCO2 conditions illustrate that Tg and viscosity decrease at higher supercritical pressure. Thermally stable and high molecular weight copolymers are successfully obtained. Tg shows a strong correlation with the carbonate linkage content of obtained PCHC chains. ScCO2 is found to remove the residual catalyst in an environmentally friendly way.